Teaching primary mathematics : a guide for newly qualified & student teachers - Aske, Mide. (British : Hodder arnorld, 1998)
Written with newly-qualified teachers and those in initial teacher training in mind, this book gets to grips with the new National Curriculum for Mathematics at Key Stages 1 and 2.
Includes bibliographical references.
Keywords: Mathematics -- Study and teaching (Elementary) -- Great Britain; Mathematics -- Study and teaching (Elementary)